Effects of Low-molecular-weight Glycyrrhiza Polysaccharides on Immune Function, Gut Microbiota and Metabolites in Healthy Mice - Shengnan XUE; Wangdi SONG; Yunyun WANG; Yan ZHANG; Genlin ZHANG (Shipin gongye ke-ji)
Objective: The effect of low-molecular-weight Glycyrrhiza polysaccharide (GP) on immune function, gut microbiota structure, and metabolites of healthy mice was studied. Methods: After 42 days of oral administration of GP (200 mg/kg) in mice, serum immune factors and hepatic antioxidant capacity were determined by enzyme-linked immunosorbent assay (ELISA). The composition of intestinal flora was analyzed by high-throughput sequencing. The content of short chain fatty acids (SCFAs) in feces was determined by gas chromatography. Results: GP significantly increased the number of goblet cells (19.12%) (P<0.05) to promote mucin production, and improved intestinal barrier function. GP significantly reduced the content of pro-inflammatory factor IL-1β (14.80%) (P<0.05), thereby enhancing the body's immune defense. In addition, GP increased the total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) levels in liver tissue by 18.18% and 73.54% (P<0.05), respectively, thus enhancing the antioxidant capacity of the liver. The results of 16S rDNA sequencing indicated that beneficial bacteria Bacteroides, Prevotellaceae_UCG-001, Parabacteroides and Muribaculum were the dominant bacteria and the relative abundance increased significantly (P<0.05) after oral administration of GP. GP upregulated the metabolic pathways of polysaccharides and coenzymes, and promoted the production of isobutyric acid (88.07%) and butyric acid (65.36%). These dominant bacteria promoted the secretion of immune cytokines and increased the antioxidant capacity of the liver, thus promoting the health of the body. Conclusion: Low-molecular-weight Glycyrrhiza polysaccharide achieved probiotic effects by enhancing the intestinal barrier function, tissue antioxidant capacity and immune response of healthy organisms, as well as changing the structure of gut microbiota and the types of metabolites.